Research assessment as governance technology in the United Kingdom: findings from a survey of RAE 2008 impacts - Oancea, A (Springer Fachmedien Wiesbaden, 2014)
This paper uses empirical research data and theoretical insights from the literature on governance to problematise some of the arguments presented in the research assessment literature, in particular, the description of the UK RAE/REF as a mechanism for top-down control with strongly negative, blanket-impacts on disciplines, institutions and individual researchers. The concepts of performativity, accountability and governmentality are employed to unpack normative claims about negative impacts and conflicts of values, and empirical claims about the nature of changes in behavior, attitude and interpretation, as reported by the researchers surveyed. The paper argues that inherent, multiple ambivalences of the RAE as a governance technology operate at the transition points between traditional and contemporary forms of governing and account for the mixed picture of its impacts at system, field, institutional, and individual level.